2013
DOI: 10.1159/000350656
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Reduced Highly Unsaturated Fatty Acids (HUFA Deficiency) in Dilative Heart Failure: Dosage of EPA/DHA and Variability of Adverse Peroxides and Aldehydes in Dietary Supplement Fish Oils

Abstract: Objectives: To explore the rationale for ω-3 fatty acids in heart failure treatment, the dosage of EPA (eicosapentaenoic acid) and DHA (docosahexaenoic acid) for replacing low levels of highly unsaturated fatty acids (HUFA deficiency) was examined. To judge the usefulness of various EPA/DHA preparations, their content of peroxides and aldehydes was determined. Methods: In 298 patients with dilative heart failure, the serum HUFA level was assessed by gas chromatography. In ω-3-acid ethyl esters 90 (Omacor/Lovaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A number of studies have recently examined fatty acid content and oxidative quality for both liquid and encapsulated formulations of EPA and DHA. Whilst certain studies concluded that the majority of products tested complied with regulations [15][16][17], others found that a notable percentage of products tested fell short in one or more quality parameters [18][19][20][21][22][23][24][25][26][27]. As the dietary supplements market has become increasingly globalized and profitable, increasing levels of dietary supplements are now available to consumers in the United Arab Emirates (UAE), and people have ready access to unfamiliar supplements that can cause unexpected adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have recently examined fatty acid content and oxidative quality for both liquid and encapsulated formulations of EPA and DHA. Whilst certain studies concluded that the majority of products tested complied with regulations [15][16][17], others found that a notable percentage of products tested fell short in one or more quality parameters [18][19][20][21][22][23][24][25][26][27]. As the dietary supplements market has become increasingly globalized and profitable, increasing levels of dietary supplements are now available to consumers in the United Arab Emirates (UAE), and people have ready access to unfamiliar supplements that can cause unexpected adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the safety of fish oil dietary supplements was questioned in a New Zealand study that documented that 83% of the assessed fish oil dietary supplements exceeded the recommended peroxide value, a marker of oxidation or oil spoilage [26]. The oils in fish oil dietary supplements are highly prone to oxidation; this may render them ineffective or potentially harmful due to altered biologic activity [40,41]. It is no surprise that both the American Diabetes Association and the International Atherosclerosis Society no longer recommend fish oil dietary supplements in the prevention or treatment of cardiovascular diseases [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Because a lower dietary intake cannot account for this reduction, the endogenous production of n-3 and n-6 HUFA appeared to be involved. It was suggested that systemic HUFA supplementation compensates for an impaired endogenous synthesis in heart failure and thus exhibits beneficial effects (Rupp et al 2013). In the GISSI-Prevenzione trial, omega-3 fatty acids reduced the risk of sudden death to a greater extent in patients with depressed heart function (Macchia et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, whether an increased synthesis of 22:5n-3 from the precursor 20:5n-3 by activation of elongase-5 (Elovl5) and elongase-2 (Elovl2) (Gregory et al 2013) is parallelized by an increase of 22:4n-6 from its endogenous precursor 20:4n-6 (arachidonic acid). Although peroxisome proliferator-activated receptor (PPAR)-alpha activation was expected to raise n-3 and n-6 HUFA to a similar extent by increased delta(5)-and delta(6)-desaturase activity (Matsuzaka et al 2002a), the PPAR-alpha activator fenofibrate increased 20: 4n-6, while 20:5n-3 and 22:6n-3 were unaffected (Rupp et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation